Efficacy of body position on gastric residual in preterm infant: a systematic review and meta-analysis - Kurvatteppa Halemani; Alwin Issac; Sanjay Dhiraaj; Prabhaker Mishra (Clinical and Experimental Pediatrics, 2023)
Background Preterm babies are born before completion of 37 weeks of gestational. Compared to term neonates, preterm babies are difficult to adjust to extra uterine life and 15 million babies (11%) born before 37 weeks of gestation. Purpose This systematic review and meta-analysis aimed to evaluate evidence concerning the efficacy of body position on gastric residual volume among preterm infants. Methods We conducted a systematic search of studies trials published in PubMed, MEDLINE, CINHAL, Clinical Key, Cochrane Library, and Google scholar. Two authors independently appraised the selected randomized control trials for evaluating the effectiveness of body position on gastric emptying. This systematic review and meta-analysis was conducted based on the Cochrane risk bias assessment tool using Revman 5.3 software. Results On assessment this systematic review and meta-analysis comprised 289 preterm infants from the included 7 trials, with the sample size ranging from 20–63. The gestational age ranged from 28–37 weeks, with an average gestational age of 31.7 weeks. The age of the participants postnatal ranged from 6.6 days to 33.4 days, with an average age of 18±6 days. The weight of the participants during data collection ranged from 1,272–2,683 g, with an average of 1,795 g. Conclusion This systematic review and meta-analysis revealed that right lateral and prone position lesser gastric residual volume in comparison to preterm infants placed in supine and left lateral position.